Growth and proliferation of gram-positive staphylococci in chevon (breast) from wet markets in Quezon City, Philippines - Rogado, Jonah Dave Loorluis
Microbial quality and physico-chemical properties of raw chevon breast on retail at two wet markets located in Quezon City, Philippines - Mega-Q Mart and Litex Market - were assessed based on total plate (TPC) and gram-positive Staphylococci counts (SC), and pH and water activity levels, respectively at 2 hour intervals, for an 8 hour period. Total plate counts from both markets ranged from 7.84 to 8.34 and 7.49 to >9.40 log CFU/g, respectively. On the other hand, gram-positive Staphylococci counts (SC) obtained were from 6.31 to 7.66 and 5.92 to >8.40 log CFU/g, respectively. Conclusively, upon correlation of the mean values of TPC and gram-positive SC, resulting growth curves for both parameters gradually increased through time with all SC ranged from 6.29 to 6.84 and 6.02 to 6.37, respectively, at temperatures of 28.0 to 31.9°C. Water activity (aw), on the other hand, exhibited values of 0.90 to 0.91 and 0.89 to 0.90, respectively, with analysis temperature values of 22.5 to 25.6°C. Sampled raw chevon breast showed unacceptable quality and favorable conditions for bacterial growth based on the microbial and physico-chemical data obtained. With the improvement of the local goat industry and the prevalence of foodborne diseases, research regarding the microbial safety and quality of produced goat meat in the Philippines must be of importance. The study aims to understand gram-positive Staphylococci growth and proliferation in raw goat meat breast with emphasis on the effects of time and the physico-chemical properties inherent to the food sample.